(untitled) (Perner’s Contacts, 2020)
The issue of shared economy is currently a very topical theme in many sectors of national economy. In the field of transport, it is possible to observe the use of some principles of shared economy, especially in the context of sharing capacity of cars in passenger transport (BlaBlaCar, Zipcar, DriveNow etc.). Taking into account the situation where the number of transported parcels is growing year-on-year, there is space for using principles of shared economy in ensuring the transport of parcels. Given the situation that this issue has not been comprehensively addressed in the Czech Republic, it is necessary to verify that the conditions for implementation principles of shared economy in the Czech Republic are appropriate. The aim of the paper is to evaluate the current situation in the Czech Republic within the implementation of principles of shared economy in the parcel delivery from an external environment, specifically using PEST analysis.